Tafsir Esoterik Sebuah Model Penafsiran Ã¢â‚¬Å“ElitÃ¢â‚¬Â yang Ã¢â‚¬Å“TerlupakanÃ¢â‚¬Â - Khusnan, Muhammad Ulinnuha (Lajnah Pentashihan Mushaf Al-Qur'an, 2010)
Basically models of exegesis can be grouped into two variets, that which is exoteric or esoteric. The first model gets extraordinary support from QurÃ¢â‚¬â„¢an researchers.Ã‚Â This is evident in the number of their commentaries that until now are countless. This phenomena leaves behind the second model of exegesis, although there are several religious scholars who have examined it so that they have produced books but it can be said these works are extremely rare.Ã‚Â Nevertheless, both exoteric and esoteric exegesis have the same urgency of importance.Ã‚Â According to a number of religious scholars, such as al-Ghazali, exoteric commentary, lacking esoteric content, in several matters is not capable of fully and comprehensively under-standing the purpose of the QurÃ¢â‚¬â„¢an. For this reason, this papers seeks to analyze esoteric exegesis commencing to its conceptual constructs, legal basis and conditions to its several models of commentary.